Role of the PD-1/PD-L1 Pathway in Experimental Trypanosoma cruzi Infection and Potential Therapeutic Options - Arana, Yanina; Gálvez, Rosa Isela; Jacobs, Thomas (Frontiers in Immunology, 2022)
Chagas disease (CD) is a neglected chronic infection caused by the protozoan parasite Trypanosoma cruzi (T. cruzi). A significant portion of infected people develops cardiac or digestive alterations over a lifetime. Since several chronic infections associated with antigen persistence and inflammation have been shown to lead to T cell exhaustion, new therapies targeting co-inhibitory receptors to regain T cell activity are under consideration. In this study, we explored immune therapeutic approaches targeting the PD-1/PD-L inhibitory pathway in an experimental model for CD. Infected PD-L1 knockout mice (PD-L1KO) showed increased systemic parasitemia although no significant differences in parasite load were observed in different organs. Furthermore, we found no significant differences in the frequency of activated T cells or proinflammatory cytokine production when compared to WT counterparts. PD-L1 deficiency led to the production of IL-10 by CD8+ T cells and to an upregulation of Tim-3 and CD244 (2B4). Unexpectedly, the lack of PD-L1 did not contribute to a significantly improved T cell response to infection. Single blockade and combined blockade of PD-1 and Tim-3 using monoclonal antibodies confirmed the results observed in infected PD-L1KO mice. Taken together our results describe for the first time that the interruption of the PD-1/PD-L1 axis during T. cruzi infection does not necessarily enhance the immune response against this parasite. Its interruption favors increased levels of parasitemia and sustained upregulation of other co-inhibitory receptors as well as the production of regulatory cytokines. These results suggest that the clinical application of immune therapeutic approaches targeting the PD-1/PD-L1 axis in CD might be risky and associated with adverse events. It highlights that more research is urgently needed to better understand the immune regulation of T cells in CD before designing immune therapeutic approaches for a clinical context.